Analisis Efektivitas dan Potensi Peningkatan Penerimaan Pajak Bumi dan Bangunan terhadap Pendapatan Asli Daerah - Rohadi Utomo; Rahmaliza (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2024)
ENGLISH Diversion the transfer of Land and Building Tax management from central to regional taxes is intended to increase Original Regional Income. This research aims to determine the effectiveness of increasing Land and Building Tax revenue for Original Regional Income in Lubuklinggau City, and to analyze of Land and Building Tax management in Lubuklinggau City, especially the potential for revenue originating from Land and Building Tax. To measure the level effectiveness of Land and Building Tax revenue, data analysis of the potential and realization PBB revenue is used, while measuring the potential for increasing Land and Building Tax revenue is done by analyzing the area of potential tax areas, the selling value of tax objects, and calculating the potential based on Land and Building Tax rates with the selling value of taxable tax objects. The results of research show that in 2017-2021, Land and Building Tax revenue's effectiveness level was categorized as ineffective because the percentage of Land and Building Tax revenue realization was <60%. In 2021, the effectiveness value was 39.63%. Meanwhile, the potential for increasing Land and Building Tax revenue is significant. The current realization for 2021 was only 15.9% of the existing Land and Building Tax potential. INDONESIA Pengalihan pengelolaan Pajak Bumi Bangunan (PBB) dari pajak pusat ke daerah dimaksudkan untuk meningkatkan Pendapatan Asli Daerah (PAD). Penelitian ini bertujuan untuk mengetahui efektivitas penerimaan PBB Kota Lubuklinggau bagi peningkatan PAD Kota Lubuklinggau, serta untuk menganalisis pengelolaan PBB Kota Lubuklinggau terutama potensi penerimaan yang bersumber dari PBB. Untuk mengukur tingkat efektivitas penerimaan PBB digunakan analisis data potensi dan realisasi penerimaan PBB, sedangkan pengukuran potensi peningkatan penerimaan PBB dilakukan dengan menganalisis luas wilayah potensi pajak, objek pajak nilai jual, dan menghitung besarnya potensi penerimaan PBB berdasarkan tarif PBB dengan nilai jual objek pajak kena pajak. Hasil penelitian menunjukkan bahwa pada tahun 2017- 2021, tingkat efektivitas penerimaan PBB dikategorikan tidak efektif karena persentase realisasi penerimaan PBB <60%. Tahun 2021 nilai efektivitas sebesar 39,63%. Sementara itu, potensi peningkatan pendapatan PBB cukup besar namun persentase potensi penerimaan PBB tahun 2021 hanya 15,9% dari potensi PBB yang ada, sehingga PBB di Lubuklinggau belum optimal.